3.5ghz Of Ice Cream Cone With Bow Tie Antenna For Microwave Imaging Application - Nordin, Khairussakinah; Ali, Nadhirah; Othman, Mohd Azlishah; Abd Aziz, Mohamad Zoinol Abidin; Sulaiman, Hamzah Asyrani (Asian Research Publishing Network (ARPN), 2015)
The objectives of this paper are to design, simulate, fabricate and examine Ice Cream Cone with Bow Tie Antenna for microwave imaging application. This antenna is designed for frequency 3.5GHz and simulated using CST Microwave Studio Simulation. The antenna was fabricated on FR4 substrate with relative permittivity of dielectric constant (Ɛr), 4.6.The result of return loss, bandwidth, gain, directivity and radiation pattern are discussed in this paper. To achieve the best antenna performance, the return loss must below than -10dB and gain at 3dB. Ice Cream Cone with Bow Tie antenna is one of the design for microwave imaging application in the span of breast cancer imaging.